Cultural Heritage Management and Economic Development Programmes: Perspectives from Desert Fringes Where IGOs and NGOs Have No Locus. (August 2014) - W, G; A, J H.
Abstract : The range of organizations involved in some way with cultural heritage management stand in proxy for an equally wide range of concerns and viewpoints. While these viewpoints differ considerably in detail, we suggest that a fundamental objective of all these organizations is to ensure that an appropriate kind and degree of cultural heritage work occurs within development contexts. The last twenty years has witnessed such progress in the underlying principles of economic development (in 'developed' or 'developing' world countries) that the notion of heritage and economic development as equally necessary in order for a sustainable future is shared by all the major participants. We explicitly include the 'developers' as a participant in cultural heritage management. Our experience is that private companies sponsoring development are rarely opposed to undertaking heritage work, although they desperately want clear guidance on what this work is supposed to entail. Both heritage and development organizations have a valuable role to play in promoting sustainable economic development, but our experiences in the very differing desert fringes of Senegal and Mongolia suggests that neither alone, nor the two in concert, are truly effective, and that the role of individuals and organizations acting with professional and ethical responsibility is pivotal in this endeavour.